Print Culture During the Thirty Years’ War: A Mixture of Information and Entertainment. The Gravedigger of Leipzig, 1632 L’imprimé pendant la guerre de Trente Ans, entre information et divertissement. Le fossoyeur de Leipzig, 1632 - Félicité, Indravati (XVIIe siècle, 2023)
In September 1631, the Battle of Breitenfeld, a few kilometres north of Leipzig, saw the victory of a powerful alliance of Protestant princes. Under the aegis of Gustavus Adolphus, the evangelical camp was reassured. Following the traumatic sack of Magdeburg a few months earlier, they were able to claim the support of the elector of Saxony and of public opinion, which was shocked by the cruelty of the imperial troops. At that time, the city of Leipzig, although also under siege, was spared any military assaults, even though General Tilly, the feared leader of the Catholic League armies who had recently been appointed to command the imperial troops, was already at the gates of the city. Contemporaries wondered about the reasons for this leniency. Some saw it as the result of the city council’s negotiations with Tilly’s envoy, Egon VIII of Fürstenberg. Others believed that Tilly had changed his mind during a brief stay in the house of the gravedigger in Leipzig, although the reasons for this change of heart were unclear. Thus, the legend of the Leipzig gravedigger was born. In the gravedigger’s house, Tilly is said to have learned of his impending death, and thus to have been dissuaded from repeating the massacre perpetrated a few months earlier in Magdeburg. This article uses printed material describing this encounter to analyse the cultural developments that accompanied the military events.
CRIS-Team Scopus Importer:2024-04-04
Keywords: gravedigger; Holy Roman Empire; Leipzig; print culture; Sweden